Berücksichtigung von Börsenkursen bei der Ermittlung von Barabfindungen im Rahmen von aktienrechtlichen Strukturmaßnahmen - Klaus Henselmann; Claudia Schrenker; Nadine Winkler (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2010)
– Due to judicial decisions the stock market prices are deemed to be the lower value limit in determining the compensations within structural measures according to German stock corporation law (e.g. squeeze-out of minority stockholders). By applying other valuation methods, in particular the income approach, a higher value than the stock market price could be relevant to fix the amount of compensation. The paper analyzes expert reports on determining the adequate compensation. The study is supposed to provide an insight into the valuation practice in the recent past.
Keywords: G34; K22; K41; M42; M48; 650; Barabfindung; Börsenkurs; Beherrschungs- und Gewinnabführungsvertrag; Aktienrecht; Strukturmaßnahmen; Ertragswert; Rechtsprechung; Compensation; Stock Market Price; Squeeze-out; Control and Profit and Loss Transfer Agreement; German Stock Corporation Law; Income Approach; Judicature; Unternehmensbewertung; Squeeze-Out; Börsenkurs; Bilanzielle Bewertung; Rechtsprechung; Aktienrecht; Deutschland